Method for improving moisture resistance of gas sensor
Through the use of reactive ion etching and SF6 gas on the gas sensor, to form a ruffled chlorophytosis structure, the problem of decline in the performance of gas sensor in the high environment of humidity is solved, and a stable and efficient response under high humidity conditions are achieved.
Patent Information
- Application Number
- CN202411477149.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
Existing gas sensors have degraded performance in environments with high humidity, interference with response signals, reduced selectivity and sensitivity, and long-term exposure to high humidity conditions will damage the stability of sensor materials.
A reactive ion etcher is used to process the gas sensor, and SF6 gas is used to form a lotus-leaf papilla structure to improve the sensor's moisture resistance.
Under different humidity conditions, the response and recovery time of the gas sensor remain consistent, maintain the original gas sensitivity performance, and improve the moisture resistance of the sensor.
Smart Images

Figure CN119355062A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas sensors, and in particular to a method for improving moisture resistance of a gas sensor. Background Art
[0002] Humidity is one of the main factors affecting the performance of gas sensors. In a humid environment, water molecules will react with the sensor material or compete for adsorption sites, causing the sensor's response signal to be disturbed, thereby affecting its responsiveness and selectivity. The presence of water molecules not only interferes with the adsorption process of the target gas, but also causes a layer of water film to form on the sensor surface. This water film absorbs the target gas molecules, reducing the number of effective gas molecules that actually contact the sensor surface, thereby reducing the sensitivity of the sensor. In addition, the presence of water molecules will also cause the sensor's ability to selectively identify different gases to decrease, because water molecules can compete with a variety of gas molecules for adsorption sites, thereby affecting the sensor's selective response to specific gases.
[0003] In addition to the immediate impact on sensor performance, long-term exposure to high humidity conditions can also damage the physical and chemical stability of sensor materials and shorten their service life. Physical damage caused by humidity includes expansion, contraction, and even deformation of the material. These changes can cause the mechanical properties of the sensor to deteriorate, and in severe cases, may even cause the sensor to fail. Impaired chemical stability is reflected in corrosion or oxidation reactions on the surface of the material, which not only changes the chemical composition of the sensor, but may also cause the sensor to lose its original functional properties.
[0004] Although the existing anti-humidity strategies are diverse, they still have their own limitations: for example, although physical isolation can prevent moisture penetration by using waterproof materials or coatings, these materials often increase the design complexity and cost of the sensor, and also reduce the gas-sensitive performance of the sensor. In addition, the waterproof coating may fail due to wear or environmental factors after long-term use. Although the use of hygroscopic materials such as desiccants can directly reduce the ambient humidity, this method is difficult to achieve precise control of the local environment around the sensor. Although electronic equipment waterproof technology can protect the internal circuit from moisture, for those sensors that need to interact directly with the environment, electronic equipment waterproofing alone cannot completely solve the problems caused by humidity. In addition, there are algorithms to eliminate the impact of humidity on gas sensors, which usually involves steps such as data preprocessing, feature extraction, and machine learning models. This method can effectively improve the accuracy and stability of the sensor under different humidity conditions. However, this method also has some disadvantages. The algorithm design and implementation process is relatively complex, requiring professional data processing and machine learning knowledge, and requires more computing resources and continuous updating of algorithms.
[0005] Therefore, although current technical means have alleviated the impact of humidity on the performance of gas sensors to a certain extent, in order to achieve long-term and reliable operation in various complex practical application environments, further research and development of more effective anti-humidity solutions are needed to ensure that gas sensors can maintain accuracy and reliability under changing environmental conditions and improve the stability and credibility of measurement results. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a method for improving the moisture resistance of a gas sensor, so as to solve the problem in the prior art that while improving the moisture resistance of the sensor, the gas sensitivity performance of the sensor may be reduced.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] A method for improving the moisture resistance of a gas sensor, the specific steps are as follows:
[0009] Step 1: Prepare the nanomaterial into a concentrated slurry suspension, drop the concentrated slurry suspension onto the electrode, heat and dry the treated electrode to obtain a gas sensor;
[0010] Step 2: The gas sensor is placed in a reactive ion etcher and etched using SF6 gas to obtain a processed gas sensor;
[0011] Wherein, in the reactive ion etcher, the SF6 gas flow rate is 20-60 mL / min, the discharge power is 50W-150W, and the bombardment time of the gas sensor in the reactive ion etcher is less than 10 minutes.
[0012] Preferably, the nanomaterial is one or more of In2O3, WO3, CuO, ZnO, and MoO3.
[0013] Preferably, the nanomaterial In2O3 is obtained by the following steps:
[0014] Using DMF as a solvent, adding indium nitrate tetrahydrate and terephthalic acid thereto, wherein the molar mass ratio of indium nitrate tetrahydrate to terephthalic acid is (1:3) to (3:1); then, keeping warm in a drying oven at 140 to 180° C. for 3 to 5 hours, to obtain In-MOF;
[0015] The obtained In-MOF was washed alternately with anhydrous ethanol and ultrapure water, then dried at 50-70°C for 10-14h, and then calcined at 350-500°C for 1-3h to obtain In2O3 nanomaterials.
[0016] Preferably, the nano material WO3 is obtained by the following steps:
[0017] Dissolve WCl6 in anhydrous ethanol and perform ultrasonic treatment. The mass volume ratio of WCl6 to anhydrous ethanol is 1g:50mL. Then add 1-2mL ultrapure water for hydrolysis reaction and continue ultrasonic treatment. After the color of the solution changes from yellow to blue-green, let it stand and precipitate.
[0018] The solid precipitate obtained after filtration is dried, and then calcined at 550-650° C. for 1-3 hours to obtain WO3 nanomaterials.
[0019] Preferably, in step 1, the nanomaterial is added to anhydrous ethanol or water to prepare a concentrated slurry suspension; wherein, calculated by mass percentage, the concentration of the nanomaterial in the concentrated slurry suspension is 2.5% to 25%.
[0020] Preferably, in step 2, the bombardment time is at least 30 seconds.
[0021] Preferably, the contact angle between the surface of the gas sensor treated by the method and water is greater than 120°.
[0022] Preferably, the gas sensor treated by the method has a response of not less than 4.01 to 5 ppm H2S gas in an environment with a relative humidity of 50%, a response time of 239 s, and a recovery time of 448 s, which are substantially consistent with the response and recovery time under drying.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention uses a reactive ion etcher to process the gas sensor. The SF6 gas can form a lotus leaf papilla structure on the surface of the gas sensor, so that the gas sensor itself has a certain moisture resistance. At the same time, the SF6 reactive ion etching method for improving the moisture resistance of sensitive materials has a certain universality, and a variety of materials can have moisture resistance.
[0025] 2. The present invention also optimizes the reaction conditions of SF6 reactive ion etching. The gas sensor obtained after the treatment has basically the same response to the target gas under different humidity, that is, it has a certain moisture resistance. In addition, the response / recovery time is also consistent, and it has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the morphology of the indium oxide nanorods in Example 1 before etching.
[0027] Figure 2 This is a morphology of the papillary-like structure of indium oxide in Example 1 obtained after SF6 etching.
[0028] Figure 3This is the morphology of the tungsten oxide nanoparticles in Example 2 before etching.
[0029] Figure 4 This is a morphology of the papillary-like structure of tungsten oxide in Example 2 obtained after SF6 etching.
[0030] Figure 5 This is a statistical graph of the responses of the indium oxide sensor of comparative example 1 and the indium oxide sensor of example 1 after SF6 etching to 2 ppm hydrogen sulfide gas at different temperatures.
[0031] Figure 6 This is a dynamic curve diagram of the gas response of the indium oxide sensor of comparative example 1 to 5 ppm hydrogen sulfide at different humidity levels.
[0032] Figure 7 This is a dynamic curve diagram of the gas response of the indium oxide sensor of Example 1 to 5 ppm hydrogen sulfide at different humidity levels after SF6 etching.
[0033] Figure 8 This is a statistical graph of the response of the indium oxide sensor of comparative example 1 and the indium oxide sensor of example 1 after SF6 etching to 5 ppm hydrogen sulfide at different humidity levels.
[0034] Fig. 9 Response / recovery time of the indium oxide sensor of comparative example 1 and the indium oxide sensor of example 1 after SF6 etching.
[0035] Fig.10 This is a characterization diagram of the water contact angle of indium oxide in comparative example 1 after indium oxide and SF6 etching in example 1.
[0036] Fig.11 Characterization diagram of the indium oxide morphology and water contact angle of Comparative Example 2 after SF6 over-etching.
[0037] Fig.12 This is a dynamic curve diagram of the gas response of the indium oxide sensor of Comparative Example 2 to 5 ppm hydrogen sulfide at different humidity levels after SF6 etching for 10 minutes. DETAILED DESCRIPTION
[0038] The present invention will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.
[0039] Unless otherwise indicated in specific cases in the present invention, the numerical ranges listed herein include the upper and lower limits, and all integers and fractions within the range, and are not limited to the specific values listed when defining the range.
[0040] 1. A method to improve the moisture resistance of gas sensors
[0041] Step 1: Prepare the nanomaterial into a concentrated slurry suspension, drop the concentrated slurry suspension onto the electrode, heat and dry the treated electrode to obtain a gas sensor;
[0042] Step 2: The gas sensor is placed in a reactive ion etcher and etched using SF6 gas to obtain a processed gas sensor;
[0043] Wherein, in the reactive ion etcher, the SF6 gas flow rate is 20-60 mL / min, the discharge power is 50W-150W, and the bombardment time of the gas sensor in the reactive ion etcher is less than 10 minutes.
[0044] After discovering many problems with the anti-humidity strategy in the prior art, the present invention conceived whether it is possible to improve the gas sensor material itself, thereby improving its anti-humidity performance and ensuring that the performance of the gas sensor does not decrease when used as a sensor in a high humidity environment. Based on this, the present invention considers making the outer surface of the gas sensor into a lotus leaf papilla structure, and through this morphology, the gas sensor itself has hydrophobic and anti-humidity properties. However, after further research, the present invention found that the nano-coating technology improves its moisture resistance by forming a coating with a lotus leaf papilla structure on the surface of the gas sensor, but this method will affect the performance of the gas sensor itself; although the chemical etching technology can also form a lotus leaf papilla structure on the surface of the gas sensor, this method will cause the etching compound to remain on the surface of the gas sensor, and the stability of the gas sensor will be more affected; therefore, the present invention considers using a reactive ion etcher to process the gas sensor, but at this time the present invention finds that the gas used by the existing reactive ion etcher cannot form the required lotus leaf papilla structure on the surface of the gas sensor, so the present invention considers using other gases for etching. The present invention finds that the use of SF6 gas can form a lotus leaf papilla structure on the surface of the gas sensor, thereby enabling the gas sensor itself to have a certain moisture resistance without affecting the performance of the gas sensor itself.
[0045] In some embodiments of the present invention, SF6 gas is used for etching. In the prior art, the gases commonly used in reactive ion etching are chloride gases (such as chlorine, boron trichloride, etc.), oxygen, argon, nitrogen, and a mixture of the aforementioned gases. However, after research, the present invention found that the use of oxygen to etch the gas sensor material will increase the roughness and hydrophilicity of the material surface, thereby improving the adsorption capacity of gas molecules and the sensitivity of the sensor. However, this etching brings about an increase in performance, and as the sensor working time increases, its oxygen content will decrease, and the improvement will gradually decay. Moreover, oxygen etching increases the hydrophilicity of the material, which is unfavorable for the moisture resistance of the gas sensor. Chloride gas will introduce chloride ions into the gas sensor, which will have an adverse effect on the performance of the gas sensor itself. Therefore, the present invention further selects fluoride gases, such as CF4 and SF6, but fluoride gases are mainly used for etching of silicon and metal materials, and CF4 is used as an etching gas. Various fluorocarbon compounds will be formed during the etching process. These fluorocarbon compounds will adhere to the surface of the gas sensor, thereby adversely affecting the performance of the gas sensor; however, this phenomenon does not occur when SF6 is used. During the etching process, the sulfur element will form the compound SOF2, which will volatilize during the etching process. Very little sulfur element remains on the surface of the gas sensor, and most of the fluorine element forms volatile compounds, and a small part acts as a functional group to bring about an anti-moisture effect. Therefore, such etching treatment will not have an adverse effect on the original performance of the gas sensor. Therefore, the present invention chooses to use SF6 gas for etching.
[0046] In some embodiments of the present invention, the gas flow rate is controlled at 20 to 60 mL / min. If the gas flow rate is too low, the etching effect cannot be achieved, and it is difficult to change the morphology of the material; but if the gas flow rate is too high, the material will be over-etched, which will not only damage the material properties, but also cause the material morphology to produce changes that are not expected by the present invention, and ultimately make the treated material lack moisture resistance. Therefore, the gas flow rate can be 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min, etc., as well as all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges.
[0047] In some embodiments of the present invention, the discharge power of the reactive ion etcher is controlled between 50W and 150W. If the discharge power is too low, the material will not be able to produce the effect of morphological change; if the discharge power is too large, the material will be over-etched, which will cause the material morphology to produce the desired change effect of the present invention, and finally the treated material will not have moisture resistance, so that the material also does not have moisture resistance. Therefore, the discharge power can be 50W, 60W, 70W, 80W, 90W, 100W, 110W, 120W, 130W, 140W, 150W, etc., and all ranges and sub-ranges between the above values. It should be understood that in the implementation scheme, any of the above ranges can be combined with any other ranges.
[0048] In some embodiments of the present invention, the bombardment time of the gas sensor in the reactive ion etcher is at least 30 seconds, and the bombardment time of the material is less than 10 minutes. If the bombardment time is too short, the structure with moisture resistance cannot be formed; but if the bombardment time reaches 10 minutes, the morphology of the material changes again, forming Fig.11 In the structure shown, the tip papilla structure required by the present invention disappears, the surface morphology of the material is distributed in a grid-like manner, and the contact angle between the surface and water decreases, which is reduced compared to the appropriate time, indicating that the moisture resistance of the material has changed. Therefore, the bombardment time can be 30s, 60s, 2min, 4min, 5min, 7min, 9min, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0049] In some embodiments of the present invention, the nanomaterial is one or more of In2O3, WO3, CuO, ZnO, and MoO3. However, the nanomaterials applicable to the method of the present invention are not limited to the above nanomaterials. The sulfur and fluorine in SF6 will form various compounds (such as SOF2, etc.) during the etching process and volatilize during the etching process; moreover, after the etching is completed, the residual sulfur element on the surface of the gas sensor is particularly low and almost negligible. Even if the fluorine element remains, it will bring about an anti-humidity effect. Therefore, the use of other nanomaterials for the method of the present invention can also achieve the technical effect of the present invention.
[0050] In some embodiments of the present invention, the preparation method of the In2O3 nanomaterial does not affect the technical effect of the present invention, and the In2O3 nanomaterials prepared by the prior art are all suitable for the present invention. The preparation method of the nanomaterial In2O3 is only an example, and the specific steps are as follows:
[0051] Using DMF as a solvent, adding indium nitrate tetrahydrate and terephthalic acid thereto, wherein the molar mass ratio of indium nitrate tetrahydrate to terephthalic acid is (1:3) to (3:1); then, drying in a drying oven at 140 to 180° C. for 3 to 5 hours to obtain In-MOF;
[0052] The obtained In-MOF was washed alternately with anhydrous ethanol and water, then dried at 50-70°C for 10-14h, and then calcined at 350-450°C for 1-3h to obtain In2O3 nanomaterials.
[0053] In some embodiments of the present invention, the preparation method of WO3 nanomaterial does not affect the technical effect of the present invention, and the WO3 nanomaterials prepared by the prior art are all suitable for the present invention. The preparation method of the nanomaterial WO3 is only an example, and the specific steps are as follows:
[0054] Dissolve WCl6 in anhydrous ethanol and perform ultrasonic treatment. The mass volume ratio of WCl6 to anhydrous ethanol is 1g:50mL. Then add 1-2mL ultrapure water for hydrolysis reaction and continue ultrasonic treatment. After the color of the solution changes from yellow to blue-green, let it stand and precipitate.
[0055] The solid precipitate obtained after filtration is dried, and then calcined at 550-650° C. for 1-3 hours to obtain WO3 nanomaterials.
[0056] In some embodiments of the present invention, in step 1, the nanomaterial is added to anhydrous ethanol or water to form a concentrated slurry suspension; wherein, the concentration of the nanomaterial in the concentrated slurry suspension is 2.5% to 25% by mass percentage. The nanomaterial is mixed with a suitable solvent to ensure that the nanomaterial can be evenly dispersed in the solvent, and to ensure that a concentrated slurry suspension in which the nanomaterial is evenly dispersed is formed, so that a uniform film can be formed on the electrode surface after drop coating.
[0057] In some embodiments of the present invention, the contact angle between the treated gas sensor surface and water is greater than 120°.
[0058] In some embodiments of the present invention, the response of the gas sensor treated by the method of the present invention to 5ppm is 4.01 in dry condition, and the response time and recovery time are 243s and 446s respectively; in an environment with a relative humidity of 50%, the response of the gas sensor treated by the method of the present invention is 4.25, and the response time and recovery time are 239s and 448s respectively, indicating that the response value, response time and recovery time of the gas sensor treated by the method of the present invention are basically not affected by humidity. The gas sensor treated by the method of the present invention has a relatively consistent response in a 6-week long-term stability test of 500ppb hydrogen sulfide gas at 50% relative humidity.
[0059] 2. Examples and Comparative Examples
[0060] Embodiment 1:
[0061] A certain amount of 30 mL DMF solution was added to a beaker, and then 1 mmol of indium nitrate tetrahydrate (In(NO3)3·4H2O) and 1 mmol of terephthalic acid H2BDC were dissolved in the DMF solution. After magnetic stirring, the solution was transferred to a stainless steel autoclave lined with Teflon and stored in a forced air drying oven at 160°C for 4 hours. The obtained In-MOF was washed alternately with anhydrous ethanol and deionized water, and then dried in an oven at 60°C for 12 hours. The dried In-MOF was placed in a quartz boat and calcined in a tube furnace at 400°C for 2 hours to obtain In2O3 nanorods.
[0062] Add 5mg of In2O3 nanomaterials to a centrifuge tube containing 200μL of C2H5OH to form a concentrated material slurry. Use a pipette to take 5μL of the suspended liquid of the gas sensing material and apply it on the interdigital electrode. Dry the In2O3 sensor on a heating table to obtain the In2O3 sensor. Etch it with SF6 gas in a reactive ion etcher to prepare the SF6-In2O3 sensor. The SF6 gas flow rate of the device is 40 ml per minute and the discharge power is 100W. The sensor was bombarded for 5 minutes and named In2O3:SF6-5.
[0063] Embodiment 2:
[0064] 0.8 g of WCl6 was dissolved in 40 mL of ethanol and ultrasonicated, then 1 mL of ultrapure water was added for hydrolysis reaction and ultrasonication was continued. After the color of the solution changed from yellow to blue-green, it was allowed to settle for 24 hours. The precipitate was filtered and dried. The dried material was placed in a quartz boat and placed in a tube furnace and calcined at 600 ° C for 2 hours to obtain WO3.
[0065] The WO3 material is formed into a thick slurry, and the suspension is dropped onto the interdigital electrodes. The sensor is dried on a heating table, and the resulting sensor is etched with SF6 gas in a reactive ion etcher to prepare the SF6-WO3 sensor. The SF6 gas flow rate of the device is 40 ml per minute, the discharge power is 100 W, and the sensor is bombarded for 5 minutes.
[0066] Embodiment 3:
[0067] The improvement is made on the basis of Example 1, except that the SF6 gas flow rate is 30 ml per minute, the discharge power is 80 W, the sensor is bombarded for 5 minutes, and the other steps are exactly the same as those in Example 1.
[0068] Embodiment 4:
[0069] The improvement is made on the basis of Example 3, except that the flow rate of SF6 gas is 20 ml per minute. The other steps are exactly the same as those in Example 3.
[0070] Embodiment 5:
[0071] The improvement is made on the basis of Example 2, and the difference therefrom is that the flow rate of SF6 gas is 20 ml per minute. The other steps are exactly the same as those of Example 2.
[0072] Embodiment 6:
[0073] An improvement is made on the basis of Example 1, and the difference therefrom is that the discharge power is 50W.
[0074] Embodiment 7:
[0075] An improvement is made on the basis of Example 1, and the difference therefrom is that the discharge power is 150W.
[0076] Embodiment 8:
[0077] An improvement is made on the basis of Example 1, except that the sensor is bombarded for 3 minutes.
[0078] Comparative Example 1
[0079] An improvement is made on the basis of Example 1, and the difference therefrom is that the gas sensor is not subjected to etching treatment.
[0080] Comparative Example 2
[0081] The method is improved on the basis of Example 1, except that the bombardment time is 10 min. The other steps are exactly the same as those in Example 1.
[0082] Comparative Example 3
[0083] An improvement is made on the basis of Example 2, and the difference therefrom is that the gas sensor is not subjected to etching treatment.
[0084] 3. Performance Comparison
[0085] The performance of the embodiments and the comparative examples were compared. The gas sensors of embodiments 1 to 8 and comparative examples 1 to 5 were tested under dry conditions and high humidity conditions respectively:
[0086] 1. Comparison Figure 1 and Figure 2 It can be seen that after being treated by the method of the present invention, the appearance of the indium oxide nanorods changes, forming many pointed papillary structures; Figure 3 and Figure 4 Similarly, the originally prepared tungsten oxide nanoparticles are very fine and have a relatively smooth surface. After being treated by the method of the present invention, the tungsten oxide forms a pointed papillary structure, and Figure 2 This indicates that the method of the present invention can significantly change the microscopic morphology of nanomaterials, so that different nanomaterials can form similar tip papilla structures.
[0087] 2. Taking Example 1 and Comparative Example 1 as examples, Figure 5 It can be seen that at different temperatures, for hydrogen sulfide gas with a concentration of 2 ppm, Example 1 has a significantly higher response performance than Comparative Example 1, which shows that the method of the present invention can improve the response performance of the gas sensor at different temperatures; and the method of the present invention can also reduce the optimal operating temperature of the gas sensor, such as Figure 5 As shown in Figure 2, reducing the temperature from 300°C to 250°C is more conducive to the application of gas sensors; at the same time, Figure 8-9 It can be seen that under different humidity conditions, the hydrogen sulfide gas with a concentration of 5 ppm was tested, which also proves that the response and recovery time of the gas sensor that has not been treated by the method of the present invention will be affected by humidity, while the response / recovery time of Example 1 under dryness and humidity is consistent, indicating that it has moisture resistance.
[0088] 3. In a dry environment, the response of the embodiment of the present invention to a concentration of 5 ppm hydrogen sulfide is 4.01, and the response time and recovery time are 243s and 446s, respectively; in an environment with a relative humidity of 50%, the response of the embodiment of the present invention to a concentration of 5 ppm hydrogen sulfide is 4.25, and the response time and recovery time are 239s and 448s, respectively; it can be seen that the performance of the gas sensor treated by the method of the present invention is not affected under high humidity conditions, and the performance gap with that in a dry environment is not large, and the original gas-sensitive performance can be significantly maintained.
[0089] 4. The gas-sensitive performance of the comparative examples in high humidity environments was significantly affected. The response value, response time and recovery time of the gas sensors in the comparative examples were not as good as those in dry environments. For example, the response of comparative example 1 to 5 ppm hydrogen sulfide gas in a dry environment was 3.22, and the response time and recovery time were 177s and 340s, respectively. However, in an environment where the relative humidity reached 50%, the response of the gas sensor in comparative example 1 dropped to 2.18, and the response time and recovery time were 242s and 383s, respectively. This shows that a high humidity environment can have an adverse effect on the performance of the gas sensor.
[0090] 5. Different etching conditions will have different effects on the moisture resistance and original performance of the gas sensor. For example, when the etching time is too long (up to 10 minutes), the response of the gas sensor treated in Example 2 to 5 ppm hydrogen sulfide in a dry environment is 4.88, but when the relative humidity is increased to 75%, the response value of the gas sensor decreases significantly to only 2.1. At the same time, by comparing Example 2 with Example 1, it can be further found that the surface morphology of the gas sensor in Example 2 has further changed due to the long etching time, from Figure 2 and Fig.11 It can be seen from the comparison that due to the long etching time, the original pointed papillary structure on the surface of Example 1 disappears, and instead a smoother mesh structure is formed. The contact angle between the surface of the gas sensor in Example 2 and water is significantly reduced, and Example 2 shows a more hydrophilic change. This is also the reason why the moisture resistance of the gas sensor in Example 2 to hydrogen sulfide gas is unfavorable.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.
Claims
1. A method for improving the moisture resistance of a gas sensor, characterized in that: The specific steps are as follows: Step 1: Prepare the nanomaterial into a concentrated slurry suspension, drop the concentrated slurry suspension onto the electrode, heat and dry the treated electrode to obtain a gas sensor; Step 2: The gas sensor is placed in a reactive ion etcher and etched using SF6 gas to obtain a processed gas sensor; Wherein, in the reactive ion etcher, the SF6 gas flow rate is 20-60 mL / min, the discharge power is 50W-150W, and the bombardment time of the gas sensor in the reactive ion etcher is less than 10 minutes.
2. The method according to claim 1, characterized in that: The nanomaterial is one or more of In2O3, WO3, CuO, ZnO, and MoO3.
3. The method according to claim 2, characterized in that: The nano material In2O3 is obtained by the following steps: Using N,N-dimethylformamide (DMF) as a solvent, adding indium nitrate tetrahydrate and terephthalic acid thereto, wherein the molar mass ratio of indium nitrate tetrahydrate to terephthalic acid is (1:3) to (3:1); then, keeping warm in a drying oven at 140 to 180° C. for 3 to 5 hours, to obtain an indium-based metal organic framework In-MOF; The obtained In-MOF was washed alternately with anhydrous ethanol and ultrapure water, then dried at 50-70°C for 10-14h, and then calcined at 350-500°C for 1-3h to obtain In2O3 nanomaterials.
4. The method according to claim 2, characterized in that: The nano material WO3 is obtained by the following steps: Dissolve WCl6 in anhydrous ethanol and perform ultrasonic treatment. The mass volume ratio of WCl6 to anhydrous ethanol is 1g:50mL. Then add 1-2mL ultrapure water for hydrolysis reaction and continue ultrasonic treatment. After the color of the solution changes from yellow to blue-green, let it stand and precipitate. The solid precipitate obtained after filtration is dried, and then calcined at 550-650° C. for 1-3 hours to obtain WO3 nanomaterials.
5. The method according to claim 1, characterized in that: In step 1, the nanomaterial is added into anhydrous ethanol or ultrapure water to prepare a concentrated slurry suspension; wherein, calculated by mass percentage, the concentration of the nanomaterial in the concentrated slurry suspension is 2.5% to 25%.
6. The method according to claim 1, characterized in that: In step 2, the bombardment time is at least 30 s.
7. The method according to claim 1, characterized in that: The contact angle between the surface of the gas sensor treated by the method and water is greater than 120°.
8. The method according to claim 1, characterized in that: The gas sensor treated by the method has a response of not less than 4.01 to 5 ppm H2S gas in an environment with a relative humidity of 50%.